Insight on infant feeding among mothers of rural community: a cross sectional study - Vasudevareddy, Savitha Sondekere; Thimmajja, Sunanda Govinder; Giriyappa, Nagarathnamma (International Journal Of Community Medicine And Public Health, 2022)
Background: India, a low-middle income and a developing country is combating with a triple burden of malnutrition with a very cost-effective measure, infant and young child feeding practices. But there are a lot of challenges in its implementation which need to be catered. Methods: A cross sectional study was aim to assess the knowledge and knowledge on practices of infant feeding among mothers of rural community. The mothers were included in the study were having children age between 0-1 year, who visits to primary health centers for availing health need services. Total 400 mothers were selected for the study by using purposive sampling method based on inclusive criteria. Results: The results shows that though it was encouraging to note that mothers were largely in favour of breast feeding, but majority 96.50% of mothers knowledge on infant feeding was inadequate, only 3.50% of mothers were found moderate level of knowledge on infant feeding, none of the mothers were found adequate level of knowledge on infant feeding. Conclusions: Regarding knowledge of infant feeding practices majority (94.25%) were identified in-adequate in their knowledge on practices of infant feeding, only (5.75%) having moderate level of knowledge on practices of infant feeding and none of the mothers found adequate knowledge of practices on infant feeding.